Rise and Learn: Understanding the Morning Shift from the Perspectives of Students - Angga, Paulino; Elminero, Hazzell (Journal of Interdisciplinary Perspectives, 2025)
This study addressed the challenges experienced by morning shift students, focusing on their academic performance and well-being. It examined issues such as disrupted sleep-wake cycles, reduced energy levels, and difficulties maintaining focus during early lectures. External factors, including rush hour traffic, early bedtimes, and persistent morning grogginess, compounded these challenges, contributing to social isolation and limited engagement with complex topics. The study also highlighted difficulties in achieving peak alertness due to late-night commitments, time management struggles, and balancing home responsibilities with academic demands, underscoring the gap in understanding how morning shift schedules impact students holistically. A qualitative research design was employed, using interviews to gather in-depth perspectives from morning shift students. The findings revealed that effective strategies, including consistent sleep patterns, calm evening routines, efficient time management, and proper hydration, significantly enhanced students’ readiness and performance. Personalized approaches, such as active learning techniques, nutrient-rich meals, and time-blocking strategies, were also found to improve focus and sustain energy throughout early classes. The study concluded that addressing morning shift students' academic and well-being challenges requires a comprehensive approach. Integrating lifestyle adjustments, strategic planning, and personalized routines can enhance their learning experiences and overall health. These insights offer valuable implications for educators and administrators in optimizing support systems for morning shift learners.